Gene regulation in β-sitosterol-mediated stimulation of adipogenesis, glucose uptake, and lipid mobilization in rat primary adipocytes - Chai, Jen-Wai (Springer-Verlag, 2010)
The nutraceutical benefits of β-sitosterol (SIT) are well documented. The present study investigated the in vitro effects of SIT on adipogenesis, glucose transport, and lipid mobilization in rat adipocytes. Primary cultures of rat preadipocytes and differentiated adipocytes were used in this study. Glucose uptake was measured by the uptake of radio-labeled glucose. Adipogenesis and lipolysis were measured by oil-red-O and glycerol quantification methods, respectively. The expression of protein kinase B (Akt), glucose transporter 4 (GLUT4), hormone sensitive lipase (HSL), and phosphatidylinositol-3-kinase (PI3 K) genes in SIT-treated adipocytes were assessed by real-time reverse transcription polymerase chain reaction (RT–PCR). The data showed that SIT induced glucose uptake in adipocytes. It also stimulated adipogenesis in differentiating preadipocytes. Interestingly, although SIT displayed general insulin-mimetic activity by stimulating glucose uptake and adipogenesis, it also induced lipolysis in adipocytes. Furthermore, the SIT-induced lipolysis was not attenuated by insulin and co-incubation of SIT with epinephrine improved epinephrine-induced lipolysis. GLUT4 gene expression was highly down-regulated in SIT-treated adipocytes, compared to insulin-treated adipocytes, which was up-regulated. Insulin- and SIT-treated adipocytes showed similar levels of Akt, HSL, and PI3 K gene down-regulation. These observations suggest that the elevation of glucose uptake in SIT-treated adipocytes was unrelated to de novo synthesis of GLUT4 and the SIT-induced lipolysis is associated with the down-regulation of Akt and PI3K genes. The unique effects of SIT on the regulation of glucose uptake, adipogenesis, and lipolysis in adipocytes show that it has potential to be utilized in diabetes and weight management.